Low-energy magnon excitations and emerging anisotropic nature of short-range order in CrI3 - Jonák, Martin; Walendy, Erik; Arneth, Jan Victor; Mohamed, Mahmoud; Klingeler, Rüdiger (Physical review, 2022)
We report on the low-energy magnetic excitations and the evolution of local magnetic fields in CrI3 in a broad frequency regime of 30-330 GHz and in magnetic fields up to 15 T. Modeling the magnon branches by means of a domain-based ferromagnetic resonance model provides the microscopic parameters describing the magnetic excitations in the two-dimensional ferromagnet. Our data reveal the anisotropy gap of Δ=80 GHz at 2 K, which remarkably remains finite at TC and vanishes only above TΔ≃80 K, i.e., for T≳1.3TC. Concomitantly, anisotropic local magnetic fields are probed by a shift of the resonance lines in the same temperature regime. Well above TC, we detect short-range magnetic correlations up to 200 K. The observed changing nature of the short-range correlations at TΔ confirms the importance of spin-orbit coupling for the evolution of long-range ferromagnetism which develops from magnetically anisotropic short-range order. In addition, our analysis of the macroscopic magnetization enables to estimate the number of correlated spins well above TC as well as the in-plane magnetic correlation length ξab.
Im Titel ist die Zahl "3" tiefgestellt
Gesehen am 30.01.2023